Singing cowboy retires after 40 years (Raton Range Raton, New Mexico, 1990)
Newspaper Article on Eloy Gonzales retiring from music.
Master list item #: 4
File location is in the Raton File Cabinet
Keywords: Gonzales, Eloy; Nelson, Willie; Tubb, Ernest; Smith, Cal; Lewis, Bobby; Dickins, Jimmy; Paycheck, Johnny; Russell, Johnny; Campbell, Glen; Bush, Johnny; Gonzales, Elmer; Mayhan, Carl; Mayhan, Jo; Club 87; Mayfield Hotel; Wagon Wheel; Old Western Dance; Rodeo; U.S Army; KRTN; You can be a star; Local History; Biography; Life and Customs; Musician; Retirement; Band -- Band members; Car wreck; National TV -- You can be a star; Raton, New Mexico; Dumas, Texas; Clayton, New Mexico